BATAKO LUMPUR LAPINDO SEBAGAI ALTERNATIF MATERIAL PASANGAN DINDING - Rofikatul Karimah (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Block made of mud is a building material used in making wall for building that is made fromsand, cement, and fly ash using certain percentage mud in sand. This research aimed to know theeffect of the use of lapindo mud towards the compressive strength, the absorption of block waterwith the mud dosage in sand are: 0%, 10%, 20%, 30%, and 40%. This research was an experimentalresearch; each design was made in size 10x20x40 cm using 5% of fly ash and without fly ash.The result of this research showed that the highest compressive strength was raised in 10%mud in sand with 5% fly ash that was 195 kg/cm2 or increased about 3.44 kg/cm2 within increasingpercentage about 10.651% towards the compressive of block without lapindo mud with 5% of flyash, and was included in class I quality of block. While for the 30% and 40% mud percentage islower compared with normal compressive strength of block. The test result of water absorption oflapindo mud block showed the higher value than 20% for lapindo mud block with 5% fly ash, inframing the mud blocks as the wall, those blocks need to be soaked first because the absorptionvalue of block is higher than 20%. Lapindo mud block without 5% fly ash has bricks water absorptionless than 20%, while in framing those bricks, they don’t need to be soaked because the absorptionof brick if lower than 20%. By using fly ash in mud block, we can get the higher compressivestrength and the lower water absorption.Keyword: Porong Mud, Block, Fly Ash, Compressive Strength, Absorption